2022
DOI: 10.2147/jir.s392652
|View full text |Cite
|
Sign up to set email alerts
|

The Role of AIM2 Inflammasome in Knee Osteoarthritis

Abstract: Knee osteoarthritis (KOA), whose prevalence keeps rising, is still unsolved pathobiological/therapeutical problem. Historically, knee osteoarthritis was thought to be a "wear and tear" disease, while recent etiology hypotheses stressed it as a chronic, low-grade inflammatory disease. Inflammasomes mediated by the innate immunity systems have an important role in inflammatory diseases including KOA. A deluge of recent studies focused on the NLRP3 inflammasome with suggestions that its pharmacologic block would … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 77 publications
0
4
0
Order By: Relevance
“…Synovial macrophages also play a key role in the activation of the NLRP3 inflammasome, which is a multiprotein complex involved in the maturation and secretion of IL-1β. The activation of the inflammasome in synovial macrophages leads to further amplification of the inflammatory response in OA [33]. The use of biophysical stimulation techniques in clinical medicine has become increasingly popular as a method to promote repair and anabolic activity in tissue or to strengthen the activity of drug treatment while lessening side effects [34].…”
Section: Discussionmentioning
confidence: 99%
“…Synovial macrophages also play a key role in the activation of the NLRP3 inflammasome, which is a multiprotein complex involved in the maturation and secretion of IL-1β. The activation of the inflammasome in synovial macrophages leads to further amplification of the inflammatory response in OA [33]. The use of biophysical stimulation techniques in clinical medicine has become increasingly popular as a method to promote repair and anabolic activity in tissue or to strengthen the activity of drug treatment while lessening side effects [34].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that canonical inflammasomes and the NLRP3 inflammasome are actively involved in the pathogenesis of OA and that selective targeting of canonical inflammasomes is an emerging pharmacological strategy for OA therapy [70][71][72][73][74]. Accumulating evidence has revealed that non-canonical inflammasomes are possible players in OA pathogenesis.…”
Section: Osteoarthritis (Oa)mentioning
confidence: 99%
“…The primary pathological feature of KOA involves the breakdown and loss of articular cartilage. Different joint tissues are impacted to different extents, including remodeling of the subchondral bone, degeneration of the meniscus, weakening and looseness of ligaments, inflammation of the infrapatellar fat pad, and inflammation of the synovial membrane [ [2] , [3] , [4] , [5] ]. Furthermore, the presence of periarticular muscle atrophy plays a significant role in the progression of KOA.…”
Section: Introductionmentioning
confidence: 99%